IDENTIFIKASI PEMAHAMAN KONSEP FLUIDA DINAMIS MENGGUNAKAN FOUR TIER TEST PADA SISWA SMA - Dini Frihanderi Aprita; Bambang Supriadi; Trapsilo Prihandono (FKIP Universitas Jember, 2018)
Understanding concepts was the most important thing in learning. The purpose of learning closely related to the cognitive domain. There were still many students didn’t know about physics concept. So, we need to identify understanding of concept physics. One way to identify an understanding of physics concept was using diagnostic test, there was Four Tier Test. Four tier test was a four level multiple choice test that was developed from diagnostic tests of three level multiple choice. This identification can be used by teachers in determining strategies, models, methods, and techniques to improve students' conceptual understanding. The research method was descriptive research. The subjects of this research were done in second grade high school students of Jember Distric. Data collection techniques used in this research was test, and the instrument was four level multiple choice. The result of the research showed that the understanding of the dynamic fluid concept in high school is 22.86%, and then which 29.21% are included category misconception, 7.09% are included in the category of not understanding concept, 34.92% are included in the category partial understand, and 5.93% are include in the category can not be encoded, it is mean students didn’t complete the answer on each level.Key word: Physics, Fluid Dynamics, Understanding concepts, Four Tier Test